Hinduism: The history of Sri Maha Mariayamman Kovil Devastanam / Kalayarasi Gurusamy - Kalayarasi , Gurusamy (1988)
Sri Maha Mariayamman Kovil Devastanam is a temple which arouse interest from many people. Many factor leads to this interest which could be economic, political, social and religious. This research consists of six chapters. Chapter I contains information on introduction aims and scope of this study. Various methods were used and problems that were faced during the research are also touched in this chapter. Chapter II deals with the growth of Hindu temple in Malaysia. A brief definition on Hinduism is given and the structure and functions of a temple is also mentioned here. Chapter III is about the historical development of Sri Maha Mariayamman Kovil Devastanam. The history of the temple and how it is being managed is given. In chapter IV, rituals of the temple are given due to importance. A thorough explanation is given on matters pertaining to the various Pujas conducted by the temple and role of the temple priest, Pantaram and other staff also highlighted. Chapter V deals with the current development of the temple. An analysis on how the temple had developed from its early days to the present days is given. The current events also touched here. Chapter VI, the temples contribution is analysis and some suggestive remarks had been given on how to improve their roles. This is to ensure that Sri Maha Mariayamman Kovil Devastanam will remain as a model Hindu temple.